Saúde e qualidade de vida ao envelhecer: perdas, ganhos e um paradoxo - Fonseca, António M. (2013)
Health plays a major role in ageing process and we can approach quality of life of the older people through their health status. Despite ageing condition is not a risk in itself, it is possible to predict that losses will occur. As a result of that older people assess their health assuming the limitations inherent to those activities they value. There are functional and personal aims that explain the assessment of health status, which makes that the importance of health, more precisely the importance of perceived health in quality of life, becomes a source of controversy issue regarding the apparent paradox between certain levels of disability and reported well-being. This paper reflects some critical points of the relationship between health and psychological condition during ageing process, presenting findings of studies with Portuguese samples made by Unit of Research and Training in Adults and Elders (www.unifai.net), which the authors are members.